Effect of the Na2O–Nb2O5–P2O5 glass additive on the structure, dielectric and energy storage performances of sodium niobate ceramics. Issue 5 (May 2021) - Benyounoussy, S.; Bih, L.; Muñoz, F.; Rubio-Marcos, F.; EL Bouari, A.
Abstract: A phosphate glass Na2 O–Nb2 O5 –P2 O5 (NPP) is incorporated into NaNbO3 (NN) ceramics to examine its impact on the density, rearrangement of structural units, dielectric and energy storage features of the elaborated composites. The sodium niobate ceramic (NN) is prepared using the solid state process, whereas, the Na2 O–Nb2 O5 –P2 O5 (NPP) glasses are produced using the method of conventional melt quenching. The glass (NPP) is added to the ceramic (NN) according to the composition (100-x) NN-xNNP; (x = 0, 2.5, 5, and 7.5 %wt). The developed composites are denoted as NN-Gx where x represents the content of glass in %wt. The appropriate sintering temperature for the glass-ceramic composites was measured based on the density measurements. It was found that with the addition of glass, their density was decreased and their fritting at lower temperatures was enhanced. The obtained SST for all composites is about 900 °C. After the densification stage, Raman spectroscopy, X-ray Diffraction, Granulo-laser analysis, and scanning electron microscopy are examined to study the structural approach and the morphology of sintered NN-Gx composites. The NN-G5 composite was found to have a fine grain microstructure that was uniform. The dielectric features of the composite revealed that at ambient temperature the NN-G5 had the greatest dielectric constant. The energy storage performance of the composite was investigated from the P-E plots and the parameters of energy storage. Based on the obtained results, it was concluded that incorporating up to 5% wt. of NNP glass in sodium niobate ceramics positively affects their dielectric and energy storage performances. Abstract : Phosphate glasses, Sodium niobate, Composite, Dielectric features, Energy storage performance